Physical Characteristics of Local Light-Brown Waxy Sorghum with Varying Levels of Polishing - Rahmawati Rahmawati; Shanti Pujilestari; Julfi Restu Amelia (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Sorghum contains a high level of tannins and is known to be anti-nutritional and give rise to an astringent flavour, so polishing is needed. This study aimed to characterize local light-brown waxy sorghum from Lamongan due to varying levels of polishing. An experimental procedure with five replications was used. The results showed that the weight of 1000 grains, seed volume, bulk density, and true density one-time polishing was 20.3109±0.3606 g, 0.016±0.000 ml, 0.755±0.015 g/ml, and 1.70±0.02 g/ml, respectively, whereas the two-time polishing was 12.6072±0.6172 g, 0.010±0.000 ml, 0.843±0,011 g/ml, and 1.67±0,02 g/ml, respectively. The sorghum seed size after one-time polishing was length 4.64±0,23 mm, width 2.98±0,17 mm, height 2.38±0,08 mm, and sphericity 69.04%, whereas after two-time polishing it was 2.90±0.12 mm, 2.89±0.09 mm, 1.84±0.11 mm, and 85.82%, respectively. More polishing resulted in a decrease in 1000 seed weight, hardness, volume, porosity, and true density of sorghum. The results also revealed that sorghum was red after one-time polishing and yellow-red after two-time polishing. Tannin content was 8971.59±42.87 mg/L and 915.88±11.64 mg/L, respectively for one-time and two-time polishing. Light-brown waxy sorghum from Lamongan should be polished two-time to be developed into flour and instant sorghum rice. Keywords: Lamongan, Light-Brown Waxy Sorghum, Polishing, Physical characteristics, Tannins